Troska biskupów kujawsko-kaliskich o Jasną Górę w okresie po Powstaniu Styczniowym (1864-1914) - Czaplicki, Bronisław (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The author presents the issue of the relationships of the bishops from the Diocese of Kujawy-Kalisz to Jasna Góra in the period after the January Uprising. Negative opinions spread about these bishops were the inspiration for this research. This study was based on a critical use of sources, which are in the Russian State Historical Archive in St. Petersburg, the Archive of Jasna Góra, the Diocesan Archive in Włocławek and the State Archive in Częstochowa. The author attempted to present the situation of the bishops constrained by the requirements of the Russian state law. This law was formulated in such a way as to enslave the hierarchy of the Catholic Church and lead to the extinction of the monastic life. The Pauline monastery was threatened not only by the destructive actions of the Russian authorities but also by deepening internal crisis, which was used by the mentioned authorities. The Jasna Góra Monastery survived and was able to revive after the collapse of the tsarist rule in Częstochowa. Credit for this revival, in large part, goes to the rulers of the Diocese of Kujawy-Kalisz, who defended the monastery and at the same time tried to influence its spiritual rebirth.